OPTICAL RADIO-CHROMIC PROPERTIES OF POLYANILINE FILM IRRADIATED WITH GAMMA RADIATION - MOHAMMED AHMED ALI; E. SAION; AWAD A. AL-ZAHRANY; Y. NOORHANA; KH. MOHD. DAHLAN; A. KASSIM; K. A. RABAEH; M.H. HAMZAH (Journal of Engineering Science and Technology, 2010)
Aniline hydrochloride monomer has been polymerized to polyaniline salt (emeraldine salt) and the characterization reveal that it is an electro-chromic material after direct -radiation exposure to high dose up to 50 kGy. The electro-chromic material which deduced by direct step wise appearance of light green color to dark green color following the radiation doses rather than colorless. The Radio-chromic and polymerization confirmed by using UV-visible spectroscopy, which gave rise to absorbance band at 790 nm, the absorbance band in turn increased following the dose exponentially. The band gap energy of PANI was obtained and showed to be decreases by increase of radiation dose down to 1 eV at 50 kGy. Raman spectroscopy showed a new bond C=N as a part of polaron conducting species is created by irradiation, which has Raman shift of 1637 cm-1. The double bond at C=N which is responsible for the appearance of the green color has been increases exponentially following the radiation dose.